Соціокультурне середовище і лідерство - Філіпчук, Георгій (НТУ "ХПІ", 2017)
Розглядаються проблеми суспільної значимості формування якісних характеристик лідера у вимірі цивілізаційного й національного розвитку. Аналізуються соціально-педагогічні, політичні, етичні, культурологічні аспекти взаємовпливів середовища, особистості, освітніх систем в контексті творення явища лідерства.

The problems of social significance of the leaders’ qualitative formation characteristics in the framework of civilization and national development are considered. The social and pedagogical, political, ethical, cultural aspects of interactions of the environment, personality and educational systems in the context of leadership phenomenon creation are analyzed.
Socio-cultural environment and leadership
Keywords: нооетика; національна культура; освіта; виховання нації; діалог культур; людський капітал; сталий розвиток; ethics; national culture; education; human capital